1999
DOI: 10.1128/jb.181.23.7331-7338.1999
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Motility in Mycobacteria

Abstract: Mycobacteria are nonflagellated gram-positive microorganisms. Previously thought to be nonmotile, we show here thatMycobacterium smegmatis can spread on the surface of growth medium by a sliding mechanism. M. smegmatis spreads as a monolayer of cells which are arranged in pseudofilaments by close cell-to-cell contacts, predominantly along their longitudinal axis. The monolayer moves away from the inoculation point as a unit with only minor rearrangements. No extracellular structures such as pili or fimbriae ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
3
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 39 publications
(41 reference statements)
5
103
3
3
Order By: Relevance
“…Biofilm-producing strains showed a sigmoid growth curve, as previously described for collection strains (Fig. 2) (13). No species differences in growth curves were detected.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Biofilm-producing strains showed a sigmoid growth curve, as previously described for collection strains (Fig. 2) (13). No species differences in growth curves were detected.…”
Section: Resultssupporting
confidence: 80%
“…A motility assay was performed as described by Martinez et al [13]. A colony of each strain was inoculated in the centre of a plate of motility medium (Middlebrook 7H9 (BD, Franklin Lakes, NJ, USA) with 0.3% agar (BD) and without supplements).…”
Section: Sliding Motility Testmentioning
confidence: 99%
“…Mycobacteria achieve spreading on surfaces by a sliding mechanism. This form of motility is likely to play an important role in the surface colonization in the environment as well as in the host [187]. The surface properties of cells, in particular determined through glycopeptidolipids, severely affect their ability to spread on solid surfaces [187][188][189].…”
Section: Biofilmsmentioning
confidence: 99%
“…Previous studies have shown that GPL-defective mutants like mps [coding for nonribosomal peptide synthetase (Billman-Jacobe et al, 1999;Recht et al, 2000)] and mtf1 [coding for methyl transferase (Recht & Kolter, 2001)] had rough colony morphology. Differences in colony morphology were also shown to be associated with sliding motility (Martinez et al, 1999;Recht & Kolter, 2001;Etienne et al, 2005) and biofilm formation (Recht & Kolter, 2001). We examined the same by assessing the surface spreading assay and attachment of mycobacterial cells to polystyrene surface.…”
Section: Analysis Of Sliding Motility and Biofilm Formation Of Merodimentioning
confidence: 99%